1999
DOI: 10.1182/blood.v93.9.2807
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Pharmacological Properties of Carbohydrate Remodeled Recombinant and Placental-Derived β-Glucocerebrosidase: Implications for Clinical Efficacy in Treatment of Gaucher Disease

Abstract: The objective of these studies was to characterize the macrophage mannose receptor binding and pharmacological properties of carbohydrate remodeled human placental-derived and recombinant β-glucocerebrosidase (pGCR and rGCR, respectively). These are similar but not identical molecules that were developed as enzyme replacement therapies for Gaucher disease. Both undergo oligosaccharide remodeling during purification to expose terminal mannose sugar residues. Competitive binding data indicated carbohydrate remod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(16 citation statements)
references
References 30 publications
2
14
0
Order By: Relevance
“…Small clinical trials showed improvement in the clinical and biochemical features of the disease [5] . Later, recombinant α-mannosyl-terminated human GCase (imiglucerase, Imig) was developed and was shown to have biologic and therapeutic equivalency to alglucerase [6] , [9] . This therapy has become the standard of care for significantly involved patients with Gaucher disease type 1 [8] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Small clinical trials showed improvement in the clinical and biochemical features of the disease [5] . Later, recombinant α-mannosyl-terminated human GCase (imiglucerase, Imig) was developed and was shown to have biologic and therapeutic equivalency to alglucerase [6] , [9] . This therapy has become the standard of care for significantly involved patients with Gaucher disease type 1 [8] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Vela has the wild type sequence with an arginine at position 495. Previously, the exchange of the histidine and arginine at position 495 was shown to have no effect on any in vitro physicokinetic properties [9] , [28] , or on the crystal structure [17] , [29] .…”
Section: Introductionmentioning
confidence: 99%
“…Receptors for mannose are abundant in Kupffer cells, alveolar macrophages, peritoneal macrophages, splenic macrophages and brain macrophages (microglia, astrocytes, and dendritic cells derived from monocyte). [ 37a,49 ] The mannose‐transmembrane receptor present in dendritic cells and macrophages is a 17d kDa C‐type lectin protein. [ 37b,50 ] These mannose‐based receptors fulfill a vital role in modulating the immune response of the host via a strong involvement in phagocytosis, antigen presentation and processing, intracellular signaling and cell migration.…”
Section: Importance Of Lectin Receptors In Glycotherapymentioning
confidence: 99%
“…[ 37a,49 ] The mannose‐transmembrane receptor present in dendritic cells and macrophages is a 17d kDa C‐type lectin protein. [ 37b,50 ] These mannose‐based receptors fulfill a vital role in modulating the immune response of the host via a strong involvement in phagocytosis, antigen presentation and processing, intracellular signaling and cell migration. [ 37c,38a,51 ] More specifically, a high density of the mannose transmembrane receptors can be observed on the surface of dendritic cells.…”
Section: Importance Of Lectin Receptors In Glycotherapymentioning
confidence: 99%
See 1 more Smart Citation